Living Madhhab Moderation In Modern Islamic Boarding Schools: Dynamics Of Islamic Legal Thought At Pondok Modern Darussalam Gontor 11 Poso - Irsyad Abd Raziq; Usman Jafar; Abdul Wahid Haddade; Rian Hidayat (Yayasan Azhar Amanaa Yogyakarta, 2026)
Diversity of legal schools is an inherent characteristic of Islamic legal tradition, yet its management in Islamic educational institutions has largely been examined from a normative perspective. Limited attention has been given to how madhhab moderation is institutionalized as an educational culture. This study investigates the implementation of Living Madhhab Moderation in Pondok Modern Darussalam Gontor 11 Poso, the dynamics of Islamic legal thought cultivated within the institution, and its implications for the intellectual character formation of students. This research employed a qualitative approach within the framework of empirical Islamic law. Data were collected through in-depth interviews, participant observation, and document analysis involving school leaders, teachers, and students. Thematic analysis was conducted using the theoretical perspectives of wasatiyyah, fiqh al-ikhtilaf, and living Islamic law. The findings demonstrate that madhhab moderation is institutionalized through curriculum integration, comparative jurisprudence learning, academic dialogue, teacher role modeling, and the daily educational culture of the boarding school. The dynamics of Islamic legal thought are developed through mastery of classical Islamic texts, principles of Islamic legal methodology, structured scholarly discussions, and continuous training in legal reasoning. These processes cultivate students who appreciate methodological diversity in Islamic jurisprudence, demonstrate critical legal reasoning, respect the ethics of scholarly disagreement, and respond constructively to contemporary Islamic legal issues. The study further reveals that the sustainability of madhhab moderation depends on an integrated institutional culture that combines academic excellence, religious values, and social responsibility. This study proposes Living Madhhab Moderation as a conceptual framework explaining madhhab moderation as a lived practice of Islamic law embedded within the educational system of modern Islamic boarding schools. The framework contributes to the development of empirical Islamic legal studies and provides a theoretical foundation for designing more inclusive, dialogical, and context-responsive Islamic education.